Method for constructing high-porosity dual-network porous material by using foam template with stable surfactant
By using glutaraldehyde and soluble polymer stabilized foam templates in the preparation of porous materials, and combining free radical polymerization reactions of water-soluble polymerized monomers, the problems of high energy consumption, cumbersome steps and low porosity in the existing porous material preparation methods are solved, and the preparation of porous materials with high porosity and high mechanical strength is achieved.
Patent Information
- Application Number
- CN202411993608.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing porous material preparation methods have problems such as high equipment requirements, high energy consumption, cumbersome steps and low porosity. In particular, foam templates are prone to instability during use, resulting in low porosity and high density.
By dissolving soluble polymers, crosslinking agents, water-soluble polymeric monomers, initiators and surfactants in water, adding glutaraldehyde for stirring and foaming, forming a water-based foam, and then polymerizing and drying, a high porosity binet porous material is obtained.
The preparation of porous materials with high porosity and high mechanical strength is achieved, which simplifies the process flow, reduces energy consumption, and improves the application prospects of materials.
Smart Images

Figure CN119684669A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous material preparation, and in particular to a method for constructing a high-porosity double-network porous material using a surfactant-stabilized foam template. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, the commonly used methods for constructing lightweight, high-porosity three-dimensional porous materials include freeze-drying, 3D printing technology, pore-forming agent etching and emulsion template technology, but these methods have high requirements for equipment, high energy consumption in the production process, cumbersome steps, and large secondary pollution, which is not conducive to large-scale production and application expansion. Foam is a gas-liquid dispersion system, and after the liquid film is fixed, a porous gel foam encapsulating the gas can be obtained. The introduction of gas can form pores in situ inside the material, and there is no need for the cumbersome steps of removing the pore-forming agent later. Using foam gel as a template to construct porous materials is a greener and simpler method.
[0004] However, the foam system is very easy to become unstable during use as a template, so the stability of the foam is the key to its template function. Generally, amphiphilic particles and molecules can be used as foam stabilizers. Amphiphilic particles can be irreversibly adsorbed at the gas-liquid interface and form an interfacial elastic film to hinder the further diffusion of gas molecules, showing good foam stability. However, the porous materials obtained from the particle-stabilized foam template usually have the problems of low porosity and high density, which limits the development of its application. A wide variety of soluble amphiphilic molecules such as surfactants are also commonly used to stabilize the gas-liquid interface. By gelling the liquid film, high-porosity porous materials can be further obtained, but the surfactant molecules can easily detach from the gas-liquid interface, resulting in the instability of the foam template. Therefore, how to ensure the stability of the surfactant-stabilized foam template during use is very critical for the preparation of high-porosity porous materials. Summary of the invention
[0005] In view of this, the present invention provides a method for constructing a high-porosity double-network porous material using a surfactant-stabilized foam template. The method provided by the present invention is environmentally friendly and has low energy consumption, and can prepare a porous material with high porosity and high mechanical strength.
[0006] In a first aspect, the present invention provides a method for constructing a high-porosity double-network porous material using a surfactant-stabilized foam template, comprising the following steps:
[0007] Dissolving a soluble polymer, a crosslinking agent, a water-soluble polymer monomer, an initiator and a surfactant in water, then adding glutaraldehyde, stirring and foaming to obtain a water-based foam; the soluble polymer can form a chemical bond with the glutaraldehyde;
[0008] The water-based foam is subjected to polymerization reaction, and then dried after the polymerization reaction is completed, so as to obtain a high-porosity double-network porous material.
[0009] Preferably, the soluble polymer is selected from chitosan or polyvinyl alcohol.
[0010] Furthermore, when the soluble polymer is chitosan, chitosan is dissolved in water in the form of chitosan-acetic acid aqueous solution, and the step of removing acetic acid is also included after the polymerization reaction is completed.
[0011] Preferably, the crosslinking agent is N,N'-methylenebisacrylamide; the water-soluble polymerizable monomer is selected from one or both of acrylic acid and acrylamide; and the initiator is selected from azobisisobutylamidine hydrochloride.
[0012] Preferably, the surfactant is a zwitterionic surfactant, a cationic surfactant or a nonionic surfactant.
[0013] Preferably, in the water-based foam, the mass ratio of glutaraldehyde, soluble polymer, crosslinking agent, water-soluble polymerization monomer, initiator and surfactant is (12-20):(40-60):(5-10):(250-350):(15-25):(25-40); the mass fraction of glutaraldehyde is 0.5-1wt%.
[0014] Preferably, the stirring and foaming rotation speed is 6000-10000 r / min; and the stirring and foaming time is 40-120 s.
[0015] Preferably, the polymerization reaction temperature is 60 to 90° C., and the polymerization reaction time is 5 to 30 minutes.
[0016] Preferably, the drying temperature is 10-40°C.
[0017] In a second aspect, the present invention provides a high-porosity double-network porous material prepared by the above method.
[0018] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0019] (1) The present invention adopts a foam template method to stabilize the foam produced by the surfactant through the chemical bonding reaction between glutaraldehyde and the soluble polymer, and uses the polymer formed by the free radical polymerization reaction of the water-soluble polymer monomer and the soluble polymer as the double network skeleton to prepare a double network porous material with high porosity and high mechanical strength. The method of the present invention is simple, environmentally friendly, and has strong universality and practicality, which improves the problems of high energy consumption, complicated steps, and low material porosity in the current porous material construction method.
[0020] (2) The high-porosity double-network porous material prepared by the present invention has a porosity of more than 80%, a low density, a pore size of more than 50 μm, and a hydrophilic porous skeleton structure. It has broad application prospects in the fields of environmental governance, cell cultivation, electrochemical energy storage and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 The microscopic morphology of the CAB foam sample, CAB-CS foam sample and CAB-CS-GA foam sample in Example 1 of the present invention (a 1~ a3), bubble size (b), foaming ability (c) and foam stabilization result diagram (d), where a1 is the micromorphology of CAB foam sample, a2 is the micromorphology of CAB-CS foam sample, and a3 is the micromorphology of CAB-CS-GA foam sample;
[0023] Figure 2 It is the rheological characterization of the CAB-CS foam sample and the CAB-CS-GA foam sample in Example 1 of the present invention, wherein a is the change of storage modulus (G') and loss modulus (G") with time; b is the steady-state shear result; c is the stress scanning result;
[0024] Figure 3 These are macroscopic images of double-network porous materials prepared in Examples 3, 4 and 5 of the present invention, wherein a is Example 3, b is Example 4, and c is Example 5;
[0025] Figure 4 It is a macroscopic picture of the water-based foam (a1-a4) and the double network porous material (b1-b4) of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 2 of the present invention;
[0026] Figure 5These are scanning electron microscope images of the double-network porous materials of Comparative Example 4 and Example 2 of the present invention, wherein a is Comparative Example 4 and b is Example 2;
[0027] Figure 6 The pore size distribution (a) and porosity characterization results (b) of the double network porous materials of Comparative Example 4 and Example 2 of the present invention are shown. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] The present invention provides a method for constructing a high-porosity double-network porous material using a surfactant-stabilized foam template, comprising the following steps:
[0030] Dissolving a soluble polymer, a crosslinking agent, a water-soluble polymer monomer, an initiator and a surfactant in water, then adding glutaraldehyde, stirring and foaming to obtain a water-based foam; the soluble polymer can form a chemical bond with the glutaraldehyde;
[0031] The water-based foam is subjected to polymerization reaction, and then dried after the polymerization reaction is completed, so as to obtain a high-porosity double-network porous material.
[0032] In the above technical solution of the present invention, the surfactant has good foaming property, and a large amount of foam can be formed when stirring and foaming. Glutaraldehyde and soluble polymer can react chemically between the foam liquid film to generate a three-dimensional network structure, thereby preventing the overflow of gas molecules in the foam, and can make the bubble size smaller, avoid the merging and drainage of bubbles, thereby assisting the amphiphilic small molecule surfactant to have a good stabilizing effect on the foam template. In addition, the introduction of glutaraldehyde and soluble polymer can also prevent the foam structure from collapsing during the free radical polymerization reaction, give full play to the template effect of the foam, and the water-soluble free radical polymerization monomer undergoes polymerization reaction under the action of the initiator, and forms a three-dimensional network under the action of the crosslinking agent, thereby forming a double network skeleton together with the soluble polymer, and improving the mechanical properties of the double network porous material.
[0033] In the present invention, the soluble polymer is selected from chitosan or polyvinyl alcohol. Chitosan can react with glutaraldehyde to form a Schiff base reaction, and polyvinyl alcohol can react with glutaraldehyde to form an aldol condensation reaction. Further, when the soluble polymer is chitosan, chitosan is dissolved in water in the form of a chitosan-acetic acid aqueous solution, and after the polymerization reaction is completed, the step of removing acetic acid is also included. The present invention does not impose any special restrictions on the preparation method of the chitosan-acetic acid aqueous solution, and the preparation method commonly used in the art can be used. In the chitosan-acetic acid aqueous solution of the present invention, the mass fraction of chitosan is preferably 5 to 7wt%, and the mass fraction of acetic acid is preferably 6 to 8wt%. The present invention does not impose any special restrictions on the step of removing acetic acid. The present invention preferably neutralizes acetic acid by soaking in an alkaline solution, and removes the alkaline solution by multiple washings with deionized water.
[0034] In the present invention, the crosslinking agent is N,N'-methylenebisacrylamide; the crosslinking agent can cause crosslinking reaction between macromolecular chains to form a three-dimensional network structure, further improving the mechanical properties of the porous material. The water-soluble polymerizable monomer is selected from one or both of acrylic acid and acrylamide; the initiator is selected from azobisisobutylamidine hydrochloride.
[0035] In the present invention, the surfactant is a zwitterionic surfactant, a cationic surfactant or a nonionic surfactant. The present invention does not impose any particular restrictions on the specific type of the surfactant, and those skilled in the art can select it according to actual needs. For example, the zwitterionic surfactant can be cocopropylamide betaine (CAB), the cationic surfactant can be cetyltrimethylammonium bromide (CTAB), and the nonionic surfactant can be fatty alcohol polyoxyethylene ether (AEO).
[0036] In the present invention, in the water-based foam, the mass ratio of glutaraldehyde, soluble polymer, crosslinking agent, water-soluble polymerization monomer, initiator and surfactant is (12-20):(40-60):(5-10):(250-350):(15-25):(25-40); the mass fraction of glutaraldehyde is 0.5-1wt%, more preferably 0.5-0.7wt%.
[0037] In the present invention, the stirring and foaming speed is 6000-10000 r / min, and the stirring and foaming time is 40-120 s. The present invention does not impose any special restrictions on the stirring and foaming equipment, and the stirring and foaming equipment commonly used in the art can be used.
[0038] In the present invention, the polymerization temperature is 60-90°C, and the polymerization time is 5-30 minutes. The present invention preferably uses thermal initiation to carry out polymerization, and can also use other methods such as light initiation, redox initiation, etc. for polymerization. Those skilled in the art can choose according to actual needs.
[0039] In the present invention, the drying temperature is 10-40° C. The drying process can be carried out at room temperature, that is, natural drying, in which the water evaporates slowly, avoiding the adverse effect of heating on the structure, and no heating or freezing is required, so the energy consumption is low.
[0040] The present invention also provides a high-porosity double-network porous material prepared by the above method, the porosity of which can reach more than 80%, and has good mechanical properties, and the Young's modulus can reach more than 500 kPa.
[0041] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no particular limitation on the source of the reagents used in the following examples, and commercially available products known to those skilled in the art can be used.
[0042] Example 1
[0043] This example investigates the effects of different components on the microscopic morphology, foaming properties and stability of the foam samples.
[0044] The foam samples were prepared as follows:
[0045] (1) CAB foam sample: 0.03 g of cocopropyl amido betaine (CAB) was dissolved in 2.53 g of water to prepare a CAB aqueous solution with a mass fraction of 1.18 wt %, and then a variable speed disperser was used to stir and foam for 60 s at a speed of 8000 r / min to obtain a CAB foam sample.
[0046] (2) CAB-CS foam sample: 1.296 g of chitosan (CS) powder was added to 21.6 g of 7.4 wt% glacial acetic acid aqueous solution, and stirred and heated at 80°C for 8 h to obtain a 5.66 wt% CS-acetic acid aqueous solution. 0.8 g of 5.66 wt% CS-acetic acid aqueous solution and 1.73 g of an aqueous solution in which 0.03 g of cocopropyl amidobetaine (CAB) was dissolved were fully mixed, and then stirred and foamed at a speed of 8000 r / min for 60 s using a variable speed disperser to obtain a CAB-CS foam sample.
[0047] (3) CAB-CS-GA foam sample: 1.296 g of chitosan (CS) powder was added to 21.6 g of 7.4 wt% glacial acetic acid aqueous solution, and stirred and heated at 80°C for 8 h to obtain a 5.66 wt% CS-acetic acid aqueous solution. 0.8 g of 5.66 wt% CS-acetic acid aqueous solution and 1.53 g of an aqueous solution in which 0.03 g of cocopropyl amidobetaine (CAB) was dissolved were mixed, and finally 0.2 g of 7.5 wt% glutaraldehyde (GA) aqueous solution was added, and then a variable speed disperser was used to stir and foam for 60 s at a speed of 8000 r / min to obtain a CAB-CS-GA foam sample.
[0048] The microscopic morphology of the CAB foam sample, CAB-CS foam sample and CAB-CS-GA foam sample was observed by microscope, and the bubble size was statistically analyzed, such as Figure 1 As shown. Figure 1 From a1 (CAB), a2 (CAB-CS), a3 (CAB-CS-GA), and b, it can be seen that with the addition of chitosan and glutaraldehyde, the size distribution range of the bubbles narrowed, indicating that CS and GA helped to form stable foams with smaller sizes and more uniform distribution. The average bubble size of the foam stabilized by the surfactant (CAB) alone was about 106.12 μm. When CS or CS and GA were added, the average bubble sizes of the foam samples were approximately 54.99 μm and 48.25 μm, respectively. In other words, the bubbles in the air-liquid interface stabilized by CAB alone may merge and drain faster. In this process, the size of the air bubbles continued to increase and the distribution became irregular, resulting in rapid defoaming of the foam. With the introduction of CS, CS, and GA, the bubbles can be stabilized and protected at an early stage, so they can maintain a smaller and uniform size, which gives the foam system higher stability.
[0049] Depend on Figure 1 From the c in Figure 2, we can see that the foaming abilities of CAB, CAB-CS and CAB-CS-GA foam samples are 342.86%, 222.21% and 225.14%, respectively. This indicates that when polymer CS is introduced into CAB aqueous solution, the foaming ability decreases, which means that the high viscosity of CS liquid may hinder the diffusion of CAB surfactant molecules from the bulk phase to the interface.
[0050] Stability was assessed by the change in foam volume over time (see Figure 1d). Like most foams stabilized by small molecule surfactants, CAB foams have a short lifespan and completely collapse within 55 min. The stability of CAB-CA-GA foams is greatly enhanced by the addition of crosslinker GA compared to CAB and CAB-CS foam samples. It is speculated that the Schiff base reaction of polymer CS and crosslinker GA occurs in the CAB-CS-GA foam liquid film, forming a 3D network that blocks the escape of gas molecules and provides an ultra-stable gel foam template.
[0051] The rheological characterization of the CAB-CS foam samples and CAB-CS-GA foam samples was carried out. Figure 2 As shown in a, the storage modulus (G') and loss modulus (G") of the foam samples were first tested over time. For CAB-CS foam, within 1200 seconds, G" was greater than G', indicating that the CAB-CS foam sample exhibited liquid properties. For the foam sample with GA added, G" was also greater than G' at first, and then G' was equal to G" at 178 seconds. After that, the value of G' exceeded G", indicating that as the Schiff base reaction between CS and GA proceeded, a 3D network structure was formed in the liquid film of the CAB-CS-GA foam. The steady-state shear results showed (see Figure 2 b), all foams show shear thinning. As the shear rate increases, the apparent viscosity gradually decreases. The addition of GA gives the foam a higher apparent viscosity. For the stress sweep test of CAB-CS-GA, when the stress is low, G" and G' both maintain constant values, and G' is higher than G", this area is the linear viscoelastic region. In this region, as the stress continues to increase, G' and G" begin to decrease until they are equal, at which time the yield stress point is considered to be reached. At sufficiently high stress, G" is greater than G', showing a transition from an elastic state to a viscous state, such as Figure 2 As shown in c, within the test frequency range, the value of G' is about one order of magnitude higher than G", showing the solid-like properties of CAB-CS-GA foam. However, no linear viscoelastic region was observed for CAB-CS foam, and G" was greater than G', indicating its liquid-like properties. These phenomena further confirm the importance of Schiff base reaction in maintaining the stability of the foam template. GA can react with CS to form three-dimensional networks, which can wrap gas molecules and combine with water molecules to inhibit the occurrence of drainage and maintain the integrity of the foam template. Therefore, CAB-CS-GA foam was subsequently introduced into the construction of double-network porous materials.
[0052] Example 2
[0053] This embodiment provides a method for preparing a high-porosity double-network porous material using a surfactant-stabilized foam template.
[0054] (1) 1.296 g of chitosan (CS) powder was added to 21.6 g of 7.4 wt % glacial acetic acid aqueous solution, and the mixture was stirred and heated at 80° C. for 8 h to obtain a 5.66 wt % CS-acetic acid aqueous solution.
[0055] (2) 0.8 g of water, 0.8 g of 5.66 wt% CS-acetic acid aqueous solution (containing 0.0453 g CS), 0.4 g of 2 wt% N,N'-methylenebisacrylamide aqueous solution (MBA, containing 0.008 g MBA) and 0.2 g of acrylic acid (AA) were mixed in a 10 mL beaker. Subsequently, 0.08 g of acrylamide (AAm), 0.03 g of cocopropylamide betaine (CAB) and 0.02 g of azobisisobutylamidine hydrochloride (AIBA) were added, stirred to dissolve, and finally 0.2 g of 7.5 wt% glutaraldehyde (GA, containing 0.015 g GA) solution was added. Then, a variable speed disperser was immediately used to stir and foam for 60 s at a speed of 8000 r / min to obtain a water-based foam.
[0056] (3) The water-based foam was heated in a water bath at 80°C for 10 minutes to cause a polymerization reaction. After the reaction was completed, it was immersed in a 0.5 mol / L sodium hydroxide solution for about 5 hours, and then washed with deionized water for 3 times to remove excess acetic acid to obtain a hydrogel foam. The hydrogel foam was placed at room temperature for 12 hours to obtain a dry double-network porous material. The density was measured to be 0.198 g / cm 3 .
[0057] Example 3
[0058] The difference between this embodiment and embodiment 2 is that the cationic surfactant cetyl trimethyl ammonium bromide (CTAB) is used to replace cocopropyl amide betaine (CAB) in this embodiment. The macroscopic picture of the double network porous material prepared in this embodiment is as follows: Figure 3 As shown in a, it can be seen that the double-network porous foam material was successfully constructed.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 2 is that this embodiment uses nonionic surfactant fatty alcohol polyoxyethylene ether (AEO3) instead of coconut oil propyl amide betaine (CAB). The macroscopic picture of the double network porous material prepared in this embodiment is as follows: Figure 3 As shown in b, it can be seen that the double-network porous foam material was successfully constructed.
[0061] Example 5
[0062] The difference between this embodiment and embodiment 2 is that chitosan is replaced by polyvinyl alcohol in this embodiment, and the specific steps are as follows:
[0063] (1) Add 1.2 g of polyvinyl alcohol (PVA) to 20 g of water and heat in a water bath at 80°C for 12 h to obtain a completely dissolved PVA aqueous solution as a stock solution for later use.
[0064] (2) 0.8g of water, 0.8g of 6wt% PVA aqueous solution (containing 0.048g PVA), 0.4g of 2wt% N,N'-methylenebisacrylamide aqueous solution (MBA, containing 0.008g MBA) and 0.2g of acrylic acid (AA) were mixed in a 10mL beaker, and the pH of the solution was adjusted to 2-3 using hydrochloric acid. Subsequently, 0.08g of acrylamide (AAm), 0.03g of cocopropylamide betaine (CAB) and 0.02g of azobisisobutylamidine hydrochloride (AIBA) were added, stirred and dissolved, and finally 0.2g of 7.5wt% glutaraldehyde (GA, containing 0.015g GA) solution was added. Then, a variable speed disperser was immediately used to stir and foam at a speed of 8000r / min for 60s to obtain a water-based foam. The foam was reacted in a water bath at 80°C for ten minutes to undergo a free radical polymerization reaction, and a double network porous foam material was obtained.
[0065] The macroscopic picture of the double network porous material prepared in this embodiment is as follows: Figure 3 As shown in c, it can be seen that the double-network porous foam material was successfully constructed.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 2 is that no CS-acetic acid aqueous solution and glutaraldehyde solution are added to the water-based foam of this comparative example, and the missing mass is supplemented by water to ensure that the mass fractions of other substances remain unchanged.
[0068] Comparative Example 2
[0069] The difference between this comparative example and Example 2 is that no glutaraldehyde solution is added to the water-based foam of this comparative example, and the missing mass is supplemented by water to ensure that the mass fractions of other substances remain unchanged.
[0070] Comparative Example 3
[0071] The difference between this comparative example and Example 2 is that the amount of 7.5wt% glutaraldehyde solution added to the water-based foam in this comparative example is 0.05g (containing 3.75mg GA), and the missing mass is supplemented by water to ensure that the mass fraction of other substances remains unchanged.
[0072] Comparative Example 4
[0073] The difference between this comparative example and Example 2 is that no cocopropyl amido betaine (CAB) is added to the aqueous solution of this comparative example, and the missing mass is supplemented by water to ensure that the mass fractions of other substances remain unchanged.
[0074] Test example
[0075] 1. Macroscopic images of water-based foam and corresponding double-network porous materials:
[0076] Figure 4 The macroscopic pictures of the water-based foams (a1-a4) and the double network porous materials (b1-b4) of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 2 show that, in the absence of the crosslinking agent GA, foams can be obtained after foaming, but only gels are formed after heating to induce the free radical polymerization reaction, and the bubbles completely disappear (see Figure 4 a1-a2 and b1-b2 in Example 2), while the foam structure in the double network porous material of Example 2 is well preserved (see Figure 4 a4 and b4 in the figure), which shows that the introduction of Schiff base reaction can prevent the collapse of the foam template when the free radical polymerization reaction occurs to produce a stable double network porous material. It is worth noting that when the concentration of the crosslinking agent (GA) is too low (Comparative Example 3, GA concentration is 0.148wt%), the foam template will still disappear and only the gel is obtained (see Figure 4 a3 and b3 in Figure 5). These results indicate that the cross-linking speed of CS and GA is a key factor in maintaining the stability of the foam template to produce a dual network. In other words, the stability of the foam template should match the reaction rate of the free radical polymerization on a time scale. An appropriate GA concentration can provide a stable foam system when free radical polymerization occurs, thereby successfully constructing a dual network porous foam.
[0077] 2. Mechanical properties
[0078] The CAB-CS-GA foam sample in Example 1 was placed at room temperature to dry for 12 hours to obtain a single network foam sample CG. The Young's modulus of the single network porous material CG and the double network porous material (abbreviated as CGAA) of Example 2 was measured. The Young's modulus of the single network porous material CG was 259.02 kPa, and the Young's modulus of the double network porous material CGAA of Example 2 was 552.45 kPa. It can be seen that after the introduction of the poly (acrylamide-acrylic acid) network, the mechanical properties are significantly improved.
[0079] 3. Microstructure characterization
[0080] Porosity is a key parameter of the structural characteristics of porous materials. The microscopic morphology and pore size distribution of the porous materials constructed by Example 2 and Comparative Example 4 were analyzed by SEM observation and mercury intrusion measurement. Figure 5 The SEM image in b shows that the double network porous material prepared by Example 2 using foam as a template has a richer and interconnected porous structure. However, the double network material pore structure obtained by Comparative Example 4 without adding a surfactant and using only gel as a template is relatively dense.
[0081] Mercury intrusion measurement (mercury intrusion test) is often used to test the pore size distribution and porosity of macroporous materials. Figure 6 As shown in a and b in Figure 4, the double network gel material in Comparative Example 4 and the double network foam gel material in Example 2 both present macroporous structures, with average pore sizes of 11.10 μm and 64.16 μm, respectively, but porosities of 38.29% and 89.45%, respectively. These results strongly prove that the pore size and porosity of the porous material are greatly improved by introducing the foam template.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for constructing a high-porosity double-network porous material using a surfactant-stabilized foam template, characterized in that: The steps include: Dissolving a soluble polymer, a crosslinking agent, a water-soluble polymer monomer, an initiator and a surfactant in water, then adding glutaraldehyde, stirring and foaming to obtain a water-based foam; the soluble polymer can form a chemical bond with the glutaraldehyde; The water-based foam is subjected to polymerization reaction, and then dried after the polymerization reaction is completed, so as to obtain a high-porosity double-network porous material.
2. The method according to claim 1, characterized in that The soluble polymer is selected from chitosan or polyvinyl alcohol.
3. The method according to claim 2, characterized in that When the soluble polymer is chitosan, chitosan is dissolved in water in the form of chitosan-acetic acid aqueous solution, and the process further includes removing acetic acid after the polymerization reaction is completed.
4. The method according to claim 1, characterized in that The cross-linking agent is N,N'-methylenebisacrylamide; the water-soluble polymerizable monomer is selected from one or both of acrylic acid and acrylamide; and the initiator is selected from azobisisobutylamidine hydrochloride.
5. The method according to claim 1, characterized in that The surfactant is a zwitterionic surfactant, a cationic surfactant or a nonionic surfactant.
6. The method according to claim 1, characterized in that In the water-based foam, the mass ratio of glutaraldehyde, soluble polymer, crosslinking agent, water-soluble polymerization monomer, initiator and surfactant is (12-20):(40-60):(5-10):(250-350):(15-25):(25-40); the mass fraction of glutaraldehyde is 0.5-1wt%.
7. The method according to claim 1, characterized in that The stirring and foaming speed is 6000-10000 r / min; the stirring and foaming time is 40-120 s.
8. The method according to claim 1, characterized in that The polymerization reaction temperature is 60-90° C., and the polymerization reaction time is 5-30 minutes.
9. The method according to claim 1, characterized in that The drying temperature is 10-40°C.
10. A high-porosity double-network porous material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-stability porous foaming gel as well as preparation method and application thereof
CN116376103A
Porous object based on biopolymers having a flexible pore size, its preparation and use thereof
EP3666294A1
Porous crosslinked hydrophilic polymeric materials prepared from high internal phase emulsions containing hydrophilic polymers
US20200017655A1
Ultra-stable aqueous foams containing highly hydrophobic particles and hydrophilic polymers and their derivated functional materials
US20210108044A1
Chitosan-polyacrylamide composite porous hydrogel, preparation and use thereof, and metal ion-detecting reagent and method
US20230147119A1